Carrimycin in a Patient with Acute Myeloid Leukemia Complicated with Life-Threatening Mixed Perianal Infection: A Case Report and Literature Review - Yang X; Shen Y; Hu T; Li H; Zhang Y; Shen Y; Wu D (Infection and Drug Resistance, 2024)
Xiawan Yang,1– 3,* Yingying Shen,1– 3,* Tonglin Hu,1– 3 Hangchao Li,1– 3 Yun Zhang,1– 3 Yiping Shen,1– 3 Dijiong Wu1– 4 1Department of Hematology, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, People’s Republic of China; 2The First School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 3National Traditional Chinese Medicine Clinical Research Base (Hematology), Hangzhou, Zhejiang, People’s Republic of China; 4Department of Oncology and Hematology, Wenzhou Hospital of Integrated Traditional Chinese and Western Medicine Affiliated to Zhejiang Chinese Medicine University, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dijiong Wu; Yiping Shen, Department of Hematology, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Youdian Road No. 54, Hangzhou, 310006, Zhejiang, People’s Republic of China, Tel +86-0571-86620325, Email wudijiong@zcmu.edu.cn; shenyp_@126.comBackground: Perianal infection has a high incidence and mortality rate in patients with acute myeloid leukemia (AML). Sometimes there is a lack of effective anti-infective treatment regimens.Case Presentation: A 58-year-old male diagnosed with AML presented with secondary perianal infection and septic shock upon admission. Although multiple pathogen cultivation and antibiotic sensitivity tests indicated the presence of sensitive strains, the corresponding antibiotics were ineffective. As a last resort, carrimycin was introduced, ultimately controlling the infection and leading to disease remission.Conclusion: Carrimycin is a complementary treatment option when conventional antibiotic therapy fails. It operates through multiple mechanisms beyond its antibiotic properties and warrants further investigation.Keywords: carrimycin, perianal infection, acute myeloid leukemia, immunomodulatory